2022
DOI: 10.17507/tpls.1202.07
|View full text |Cite
|
Sign up to set email alerts
|

Applying Web-Based Technology in Developing Student Worksheets on Writing Local Culture Content Drama Script

Abstract: The purposes of this study were to identify the students’ and teacher’s needs for student worksheets for teaching local culture content drama scripts writing based on the verses of Sultan Abdul Muluk (SAM), to design a prototype of the worksheets, to obtain expert validation of the prototype, to determine the worksheets’ practicality, and to examine the effectiveness of the developed worksheets. The research procedures were based on Plomp's model and Tessmer's modified model of Research & Development. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
(21 reference statements)
0
4
0
2
Order By: Relevance
“…Akpınar focused on the mental-health concerns among students who were isolated from peers and familiar learning spaces (studios and concert halls) [26]. Several studies on relevant topics were further explored by [13] on dance, [27] on film, and Suwartono's research team on drama [28]. Nonetheless, these studies are subject-specific, and there is a lack of a holistic approach to comprehend the whole performing arts education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Akpınar focused on the mental-health concerns among students who were isolated from peers and familiar learning spaces (studios and concert halls) [26]. Several studies on relevant topics were further explored by [13] on dance, [27] on film, and Suwartono's research team on drama [28]. Nonetheless, these studies are subject-specific, and there is a lack of a holistic approach to comprehend the whole performing arts education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was also supported by negotiating texts based on local cultures in textbooks to make students closer to them in the learning process (Mokoginta & Arafah, 2022). Furthermore, the materials could also be in the form of drama scripts involving technology to elaborate the teaching and learning process and local wisdom (Nurhayati et al, 2022). It indicated that local wisdom from the studied manuscript could be used as literature teaching and learning materials in high schools following the existing basic competencies.…”
Section: B Discussionmentioning
confidence: 94%
“…They are (1) spelling and punctuation accuracy, (2) editorial clarity and readability, (3) accuracy of examples and illustrations, (4) suitability of language styles with the target students, (5) grammatical accuracy, (6) accuracy of word choice, (7) clarity of language of instruction, (8) language properness, (9) cohesion between sentences, and (10) coherence between paragraphs. (Nurhayati et al, 2022) According to this text, a good research paper includes all these requirements for disseminating the messages to the target groups. In addition, Nurhayati et al (2022) make it clear that these are unavoidable tools and methods.…”
Section: Discussion and Resultsmentioning
confidence: 99%